Genetic neuroimaging of bipolar disorder: a systematic 2017–2020 update. (April 2021) - Janiri, Delfina; Kotzalidis, Georgios D.; di Luzio, Michelangelo; Giuseppin, Giulia; Simonetti, Alessio; Janiri, Luigi; Sani, Gabriele
Abstract : There is evidence of genetic polymorphism influences on brain structure and function, genetic risk in bipolar disorder (BD), and neuroimaging correlates of BD. How genetic influences related to BD could be reflected on brain changes in BD has been efficiently reviewed in a 2017 systematic review. We aimed to confirm and extend these findings through a Preferred Reporting Items for Systematic reviews and Meta-Analyses-based systematic review. Our study allowed us to conclude that there is no replicated finding in the timeframe considered. We were also unable to further confirm prior results of the BDNF gene polymorphisms to affect brain structure and function in BD. The most consistent finding is an influence of the CACNA1C rs1006737 polymorphism in brain connectivity and grey matter structure and function. There was a tendency of undersized studies to obtain positive results and large, genome-wide polygenic risk studies to find negative results in BD. The neuroimaging genetics in BD field is rapidly expanding. Abstract : Supplemental Digital Content is available in the text.